Analisis Komparatif Undang-Undang Penanaman Modal Asing Indonesia (UU No. 25 Tahun 2007) dengan Foreign Business Act Thailand (B.E. 2542): Implikasi terhadap Daya Tarik Investasi Asing dalam Perspektif Hukum Investasi Internasional - Bunga Wahyuni (Jurnal Hukum Lex Generalis, 2026)
Investment policy plays a crucial role in attracting foreign investors to a country. This study compares foreign investment regulations in Thailand and Indonesia, based on the Foreign Business Act of 1999 and Indonesia’s Law No. 25 of 2007. Thailand enforces strict sectoral restrictions, while Indonesia adopts a more open approach through incentives and simplified licensing. Thailand excels in legal stability and cultural protection, whereas Indonesia appeals to investors seeking flexibility and innovation. The study recommends a balanced policy between national protection and global openness to enhance investment competitiveness across Southeast Asia.